THE SOUTH AFRICAN STRATEGIC AND OPERATIONAL OBJECTIVES IN ANGOLA, 1987–88 - Scholtz, Leopold (Scientia Militaria - South African Journal of Military Studies, 2011)
Ever since 1988, a war of words has been waged about the question who won the so-called Battle of Cuito Cuanavale – the SADF, or the Cuban and Angola forces. A lot depends, of course, on what the South Africans’ strategic and operational objectives were, and whether they reached these or not. On a somewhat lower level, the debate has centred on the question whether the SADF wanted to occupy Cuito Cuanavale. If they did, it becomes easier to argue that South Africa was dealt a heavy reverse there; if not, such an argument becomes more difficult to sustain. In this article, South Africa’s strategic and operational objectives are analysed, based on archival sources. The basic conclusions are that the South African government was realistic enough to see that it could not replace the MPLA with UNITA by force, although it was hoped this might happen through elections. As far as Cuito Cuanavale is concerned, the sources are unequivocal: Although the occupation of the town was indeed discussed, it was never seriously considered. The objective was simply to drive FAPLA over the Cuito River, to prepare the riverbank as a defensive line, to turn it over to UNITA and then to pull back. By far most of the South Africans’ objectives were reached.